Розширений простiр станiв рацiональної sl(2) моделi годена в термiнах полiномiв лягера - Bezvershenko, Yu. V.; Holod, P. I. (Publishing house "Academperiodika", 2018)
We consider the rational Gaudin model with non-zero magnetic field, which physically corresponds to the central spin problem. The space of states is described in terms of separated variables. The states of a spin system are given by rational (up to an exponential factor) functions of these variables on the Lagrangian submanifold. We build a representation of the sl(2) algebra of the model in terms of Laguerre polynomials and formulate the functional Bethe ansatz using it.